1994
DOI: 10.1177/0011128794040001007
|View full text |Cite
|
Sign up to set email alerts
|

A Test of the Deterrent Effect of Legislative Waiver on Violent Juvenile Crime

Abstract: The automatic transfer of juveniles charged with serious crimes to adult court has become an increasingly common alternative to juvenile court handling in a number of states in the past two decades. Deterrence is one of the major arguments underlying this growth in the use of legislative waiver. This research evaluated the deterrent effect of the 1981 Idaho legislative waiver statute. Analyses of arrest data using a time series design indicated that this law did not reduce violent juvenile crime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 11 publications
4
53
0
1
Order By: Relevance
“…Contrary to the expectations of the proponents of "get-tough" policies, previous research generally found that transfer is related to higher rather than lower rates of recidivism (Singer and McDowall 1988;Fagan 1991;Jensen and Metsger 1994;Bishop et al 1996a;Podkopacz and Feld 1996;Singer 1996;Winner et al 1997). Prior studies used samples drawn before many of the major reforms were implemented.…”
Section: Juveniles the Focus Of Tough Policiesmentioning
confidence: 94%
“…Contrary to the expectations of the proponents of "get-tough" policies, previous research generally found that transfer is related to higher rather than lower rates of recidivism (Singer and McDowall 1988;Fagan 1991;Jensen and Metsger 1994;Bishop et al 1996a;Podkopacz and Feld 1996;Singer 1996;Winner et al 1997). Prior studies used samples drawn before many of the major reforms were implemented.…”
Section: Juveniles the Focus Of Tough Policiesmentioning
confidence: 94%
“…The authors use 13-to 15-year-olds in New York as the treatment group and use 16-to 19-year-olds in New York and 13-to 15-year-olds in Philadelphia as controls. Jensen and Metsger (1994) examine the effect of a 1981 law in Idaho that required juveniles between the ages of 14 and 18 charged with serious crimes (namely, murder, robbery, forcible rape, and mayhem) to be transferred to the adult system. The authors compare the rate of total juvenile arrests in Idaho in the 4 years before and after the statute was enacted with the rate of total juvenile arrests during that period in Wyoming and Montana.…”
Section: Prior Literaturementioning
confidence: 99%
“…L'expérience de certains États américains confirme bien que des lois visant à accroître le recours au système pénal pour adultes dans le cas d'infractions violentes ne parviennent pas à réduire la délinquance violente des jeunes. En sont témoins les lois des États de New York et de l'Idaho, dont les évaluations ont clairement mené à cette conclusion (Singer et McDowall, 1988 ;Jensen et Metsger, 1994).…”
Section: De Quelques Résultats Prévisiblesunclassified